A Historical Study of the Problem of Pak Hosted Terrorism in Jammu and Kashmir - Mahesh Kumar (International journal of economic perspectives, 2022)
जम्मू कश्मीर में पाक आयोजित आतंकवाद की समस्या का एक ऐतिहासिक अध्ययन